Governing innovation projects in firms: The role of competition between innovation projects and interdepartmental collaboration - Younes Iferd; Torben Schubert (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
The existing literature shows that interdepartmental collaboration within companies en-hances innovativeness due to easier access to and integration of knowledge spread over dispersed actors. As companies are well aware of these benefits they also use competi-tion between innovation projects to organize their innovation projects. Such competitive mechanisms have often been regarded as problematic because of their adverse effects on collaboration and knowledge sharing. At the same time, they have the power to expe-dite innovation processes. Based on German CIS data, we use a stochastic frontier ap-proach to show that competition across innovation projects tends to increase innovation efficiency for firms faced by predatory product market competition, while interdepartmental collaboration is efficiency increasing when competition is low. Furthermore, we were also able to show that with increasing innovation radicalness interdepartmental collaboration enhances the innovation process and that with increasing innovation incrementality com-petition across innovation projects becomes beneficial.
urn:nbn:de:0011-n-4768884
Keywords: 330